Analyzing the Mathematical Critical Thinking Skills of High School Students in Arithmetic: A Gender Differences - Harahap, Putri Ardhanita; Dewi, Rivani Adistia; Purniati, Tia (FKIP Universitas Lampung, 2025)
Analyzing the Mathematical Critical Thinking Skills of High School Students in Arithmetic: A Gender Differences. Objective: The purpose of this investigation is to evaluate the mathematical critical thinking abilities of senior high school pupils in the field of arithmetic in relation to gender. In particular, it examines the critical thinking patterns of male and female pupils at varying ability levels (high, medium, and low) using four primary indicators: interpretation, analysis, evaluation, and inference. Methods: A qualitative descriptive methodology was implemented. A purposive selection of six tenth-grade students was made from a pool of 31 participants based on the results of an initial critical thinking test. These six pupils represented all three ability categories and both genders. Critical thinking essay assessments, semi-structured interviews, and classroom observations were implemented to accumulate data. The data was analyzed using source triangulation, reduction, and categorization in accordance with Facione's indicators. Findings: The findings indicated that female students exhibited more systematic and circumspect approaches, which led to their success in interpretation and analysis. In contrast, male pupils were more responsive but less meticulous and reflective. In terms of evaluation, the majority of students in all categories did not assess their work, which suggests that they have inadequate metacognitive abilities. Despite the fact that their final answers were accurate, numerous students were unable to articulate explicit conclusions regarding inference. High-ability students exhibited strategic planning and reflective thinking, whereas low-ability students relied on procedural and rote-based methods. Conclusion: The study emphasizes the significance of instructional strategies that are responsive to ability and gender. Integrating mathematical communication, reflection, and explicit training in evaluation and inference are critical components of effective teaching strategies that promote the development of critical thinking. According to the results, female students are more structured and reflective, whereas male students are more evaluative but less quickly. The necessity of instructional designs that are consistent with the unique characteristics of students is suggested by the fact that these differences are influenced by cognitive styles, confidence levels, and learning patterns. Keywords: mathematical critical thinking skills, high school students, gender.